(untitled) (Scientific journal of the Fergana State University, 2024)
This article covers research methods in physical education classes in general secondary education schools, academic lyceums and vocational schools, higher education institutions, movement activity of children in the process of training in general physical fitness, the use of physical qualities with the help of special exercises and vocational-theoretical knowledge on the use of action games.